0386 Long-term Safety During a Clinical Trial of Lower-Sodium Oxybate in Participants With Narcolepsy With Cataplexy. (25th May 2022) - Bogan, Richard; Foldvary-Schaefer, Nancy; Skowronski, Roman; Chen, Abby; Thorpy, Michael
Abstract: Introduction: Treatment-emergent adverse events (TEAEs) were analyzed during a 6-month open-label extension (OLE) of a double-blind, placebo-controlled, randomized withdrawal trial (NCT03030599) of lower-sodium oxybate (LXB; Xywav™). LXB is FDA approved for treating cataplexy or excessive daytime sleepiness in patients with narcolepsy aged ≥7 years and for treating idiopathic hypersomnia in adults. Methods: Participants entered the OLE following rescreening (re-entry) after discontinuing LXB treatment or directly after completing the main study (rollover). Re-entry participants initiated LXB (4.5 g/night) or, if taking sodium oxybate (SXB) during rescreening, transitioned to identical LXB doses (gram-for-gram). Participants titrated (1‒1.5 g/night/week) to a maximum of 9 g/night. TEAEs were assessed in all participants receiving ≥1 LXB dose. TEAE duration represents time from TEAE start to end date (or end of OLE, if TEAE end date unrecorded). Results: In the analysis population (N=74, mean±SD age=37.6±12.6 years, 66.2% female, 91.9% White), 27 (36.5%) re-entered (after a median [range] of 15.0 [4.0‒33.0] days), and 47 (63.5%) rolled over. Most reported ≥1 TEAE (overall, 58.1%; re-entry, 59.3%; rollover, 57.4%). Overall, the most commonly reported TEAEs were headache (n=7, 9.5%; peak incidence was month 3 [n=5/72]; median [range] duration=1.0 [1‒25] day), nasopharyngitis (n=6, 8.1%; peak incidence was month 6 [n=2/69]; median [range] duration=9.0 [1‒24] days), and dizziness (n=5, 6.8%; peak incidence was month 1 [n=3/74]; median [range] duration=26.0 [1‒181] days). TEAEs were most prevalent in month 3 (n=11/72 [15.3%] reporting a TEAE). No participant reported fall or enuresis; 1 reported nausea (rollover). Most TEAEs were mild or moderate; 2 participants had severe TEAEs (invasive ductal carcinoma [IDC], n=1; dizziness, n=1). Few participants (14.9%) had LXB-related TEAEs, most frequently dizziness (overall, 5.4%; re-entry, 7.4%; rollover, 4.3%). LXB-related TEAEs were more common in participants who re-entered (re-entry, 22.2%; rollover, 10.6%). Seven participants discontinued (re-entry, n=2; rollover, n=5), 3 due to TEAEs (IDC, n=1; apathy, n=1; sleep apnea syndrome, n=1); only apathy was treatment related. Conclusion: In this long-term study of LXB, safety and tolerability profiles were generally consistent with the known safety profile of SXB. The most common TEAEs were headache, nasopharyngitis, and dizziness. Support (If Any): Jazz Pharmaceuticals.